The dissemination of healthy eating practices: an experience report (Research, Society and Development, 2022)
Introduction: In contemporary society, healthy eating has spread among the majority of society, becoming an ally in the fight against serious diseases such as hypertension and diabetes. Objective: This article proposes to disseminate the practice of healthy eating, from the experience of students in a Basic Health Unit (UBS) to disseminate healthy eating practices in the curricular activity Attention, Management and Education in Health (AGES). Methodology: This is a descriptive study, of the experience report type, using the experience of Medicine students at UBS Frei Tito, together with social networks, for the dissemination of information on health and well-being focused on healthy eating. The experience allowed students to create an Instagram page called @freititosaudavel, spreading the culture of good eating habits. For this, materials such as the model of an artery made of "biscuit" were used to instruct the population in person about clogged arteries, pamphlets with information, photos and posters. These actions were aimed at residents of the region adjacent to the UBS, which is considered a center specializing in diabetics and hypertensive patients, located in Fortaleza. Results and Discussion: The creation of an Instagram page was obtained, helping to pass on content about good health practices with a focus on the healthy diet of the residents of the region, obtaining a satisfactory return from the target audience. Conclusion: In view of the expository actions and the media tool created to promote healthy eating, the population acquired more information and, with this, new students will be able to continue this project, feeding the instagram page and, thus, improving eating habits and quality. of life due to access to this scientific content.